Tipologia de sistemas de produção de leite de base familiar como ferramenta para orientar ações de assistência técnica - Dias, Rodrigo Diorio Souza (2011)
It was conducted a study of dairy cattle production systems of familiary based, with the goal of building types to be used to guide actions of technical assistance. The properties were located in the microregion Amerios, northwest of Paraná State, comprising the municipalities of Tapejara, Cruzeiro do Oeste, Rondon, Guaporema, Cidade Gaucha, Maria Helena, Nova Olimpia, Tuneiras do Oeste, Mariluz and Tapira. There were selected 33 farms where milk represented an important source of income and work for the family and wich also represent the typical systems in the region. Interviews were conducted with the help of a semistructured questionnaire, generating 30 variables covering climate and edaphic structural characteristics of property, family educational level livestock feedingmanagement and forage production area, each variable had from three to four levels of classification. Data were analyzed using factor analysis of multiple correspondence analysis and ascending hierarchical classification (cluster). The classification resulted in three groups as following: a) T1 group, with small territorial areas and low educational level, fed exclusively on pasture and little variation in the use of land for forage production (n =. 14); b) T2 group, with areas of medium length and average educational level, using some practical feed management and forage as one option besides the main pasture (n = 13), c) T3 group, an area with large tracts of land, average educational level, with adoption of various feeding management and forage production in summer and winter (n = 6). The results indicate significant diversity among the studied production systems and considered variables, constituting a useful guide in policy action aimed to ensure the evolution of production systems.